Proteomic Analysis of Serum Opsonins Impacting Biodistribution and Cellular Association of Porous Silicon Microparticles - Rita E. Serda; Elvin Blanco; Aaron Mack; Susan J. Stafford; Sarah Amra; Qingpo Li; Anne van de Ven; Takemi Tanaka; Vladimir P. Torchilin; John E. Wiktorowicz; Mauro Ferrari (Molecular Imaging)
Mass transport of drug delivery vehicles is guided by particle properties, such as size, shape, composition, and surface chemistry, as well as biomolecules and serum proteins that adsorb to the particle surface. In an attempt to identify serum proteins influencing cellular associations and biodistribution of intravascularly injected particles, we used two-dimensional gel electrophoresis and mass spectrometry to identify proteins eluted from the surface of cationic and anionic silicon microparticles. Cationic microparticles displayed a 25-fold greater abundance of Ig light variable chain, fibrinogen, and complement component 1 compared to their anionic counterparts. Anionic microparticles were found to accumulate in equal abundance in murine liver and spleen, whereas cationic microparticles showed preferential accumulation in the spleen. Immunohistochemistry supported macrophage uptake of both anionic and cationic microparticles in the liver, as well as evidence of association of cationic microparticles with hepatic endothelial cells. Furthermore, scanning electron micrographs supported cellular competition for cationic microparticles by endothelial cells and macrophages. Despite high macrophage content in the lungs and tumor, microparticle uptake by these cells was minimal, supporting differences in the repertoire of surface receptors expressed by tissue-specific macrophages. In summary, particle surface chemistry drives selective binding of serum components impacting cellular interactions and biodistribution.